2007
DOI: 10.3892/ijmm.20.3.373
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms in thecyclooxygenase-1 gene promoter and peptic ulcers in Japan

Abstract: Abstract. Cyclooxygenase-1 (COX-1) has been regarded as a constitutively expressed enzyme that generates prostaglandins for gastrointestinal integrity. We attempted to clarify the association between potentially functional polymorphisms (T-1676C and A-842G/C50T) in the COX-1 gene promoter and gastroduodenal disorders in a Japanese population. The study was performed with 480 stocked DNAs from subjects (gastric ulcers in 93 subjects and duodenal ulcers in 44) with no evidence of gastric malignancy. We employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 19 publications
(25 reference statements)
4
30
0
Order By: Relevance
“…We detected UGT1A6 and CYP2C9 gene variants in 43.5 and 3.0% of patients, respectively. These frequencies were similar to those in previous Japanese studies [23][24][25][26][27][28], which were lower compared with those in Western populations [20]. We found no significant association between these gene variants and peptic ulcer among patients taking low dose aspirin.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We detected UGT1A6 and CYP2C9 gene variants in 43.5 and 3.0% of patients, respectively. These frequencies were similar to those in previous Japanese studies [23][24][25][26][27][28], which were lower compared with those in Western populations [20]. We found no significant association between these gene variants and peptic ulcer among patients taking low dose aspirin.…”
Section: Discussionsupporting
confidence: 90%
“…The frequencies of the genotypes were almost the same as those of the data published previously by other Japanese investigators [3,15,23,24].…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Cytochrome P450 2C9 (CYP2C9) variants were reported to increase the risk for ulcer bleeding in NSAIDs consumers in several studies [6]. In a Japanese study, a polymorphism of the gene encoding cyclooxygenase (COX-1-1676 T allele) was associated with ulcer in NSAIDs consumers [7], while another study reported the carriage of interleukin-1β (IL-1b-511T) T allele to be associated with an increased risk for ulcer in aspirin consumers [8]. Another Japanese study has recently demonstrated an increased risk for bleeding in LDA consumers harboring the angiotensinogen variant genotype (AGT-20 CC) [9].…”
Section: Introductionmentioning
confidence: 99%